2009
DOI: 10.1210/me.2008-0217
|View full text |Cite
|
Sign up to set email alerts
|

Runx2 Recruits p300 to Mediate Parathyroid Hormone’s Effects on Histone Acetylation and Transcriptional Activation of the Matrix Metalloproteinase-13 Gene

Abstract: PTH regulates transcription of a number of genes involved in bone remodeling and calcium homeostasis. We have previously shown that the matrix metalloproteinase-13 (MMP-13) gene is induced by PTH in osteoblastic cells as a secondary response through the protein kinase A pathway requiring the runt domain and activator protein 1 binding sites of the proximal promoter. Here, we investigated the changes PTH causes in histone acetylation in this region (which contains the only deoxyribonuclease-hypersensitive sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 34 publications
4
35
1
Order By: Relevance
“…Under basal conditions, gene transcription of Mmp13 is repressed by the presence of HDAC4, which binds to Runx2 at the runt domain binding site (15). PTH treatment causes HDAC4 to dissociate from Runx2 on the Mmp13 promoter, and Runx2 then recruits the histone acetyltransferases, p300 and PCAF (13,14). Newly synthesized c-Fos/c-Jun subsequently bind to the AP-1 site and interact with CBP and with proteins bound to Runx2, allowing maximal transcription of Mmp13 (58).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under basal conditions, gene transcription of Mmp13 is repressed by the presence of HDAC4, which binds to Runx2 at the runt domain binding site (15). PTH treatment causes HDAC4 to dissociate from Runx2 on the Mmp13 promoter, and Runx2 then recruits the histone acetyltransferases, p300 and PCAF (13,14). Newly synthesized c-Fos/c-Jun subsequently bind to the AP-1 site and interact with CBP and with proteins bound to Runx2, allowing maximal transcription of Mmp13 (58).…”
Section: Discussionmentioning
confidence: 99%
“…For ChIP-reChIP assays, the immunoprecipitated complexes obtained by ChIP with anti-c-Jun antibody (Cell Signaling) were eluted in ChIP elution buffer and then diluted 5-fold and subjected to the ChIP procedure with anti-SIRT1 (Abcam) or IgG as negative control. Then the DNA was subjected to PCR with primers Ϫ84/Ϫ2 that amplified the AP-1 site of the rat Mmp13 promoter, 5Ј-ACTCACTAGGAAGTGAACAC-3Ј (forward) and 5Ј-TCCCAGGGCAAGCATTCTCTA-3Ј (reverse) (13). Input DNA (1:100) is a positive control for the assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the MMP-13 promoter in osteoblastic cells, we have shown that Runx2 binds HDAC4, resulting in a repression of transcription under basal conditions (22). After PTH treatment, HDAC4 dissociates from Runx2, which is then free to recruit p300 to activate transcription (23).…”
Section: Pthmentioning
confidence: 98%
“…Runx2 Increases Snail Expression through p300-mediated Histone Acetylation-Runx2 has been reported to associate with histone acetyltransferase p300 and then to increase the expression of the cancer invasion-related gene (23). We used the TFSearch computational tool to search for p300 binding sites in Snail promoter.…”
Section: Runx2 Is Required For Bmp-2-induced Snail Up-regulation and mentioning
confidence: 99%